2014
DOI: 10.1080/19476337.2014.984336
|View full text |Cite
|
Sign up to set email alerts
|

Usability of residual oat flour in the manufacture of extruded corn snacks

Abstract: Extrusion technology is used to produce snacks from various raw materials, including by-products. One such by-product is residual oat (Avena sativa L.) flour (ROF), which is obtained as a by-product in the production of Betaven. The aim of this study was to prepare extrudates based on cornmeal with varying proportions of ROF, and to investigate the influence of applied additives on nutritional and prohealth compounds and the texture and functional properties of the snacks. Cornmeal extrudates with varying prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…The protein content found in this research was within the range reported for high‐protein snacks, Gumul et al. (2015) from 7.71–8.98 g/100 g, Alam et al. (2016) of 10.25–14 g/100 g, Navarro‐Cortez et al.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The protein content found in this research was within the range reported for high‐protein snacks, Gumul et al. (2015) from 7.71–8.98 g/100 g, Alam et al. (2016) of 10.25–14 g/100 g, Navarro‐Cortez et al.…”
Section: Resultssupporting
confidence: 86%
“…James and Nwabueze (2013) noted that extrusion cooking significantly ( p < .05) increased ash in extrudates from 2.85 to 5.15 g/100 g, which was attributed to the high temperature of the barrel and the high cutting speed involved during the process of cooking. The ash content found in this research (1.67–7.88 g/100 g) was higher than that (0.58–2.5 g/100 g) reported by other authors (Gumul et al., 2015; Liu et al., 2017; Navarro‐Cortez et al., 2016). These differences were due to the mineral content of the raw materials used in each investigation.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…Sensory analysis of food is especially important as it provides information on potential consumer attitudes to a new product (Gumul et al, 2015). Figure S3 shows the visual appearance of the four evaluated runs (Run 1, Run 5, Run 9 and Run 14) and the processing conditions used.…”
Section: Sensory Analysismentioning
confidence: 99%